Differential susceptibility of S and M phase cyclin/CDK complexes to inhibitory tyrosine phosphorylation in yeast - Keaton, Mignon A. (2007)
BACKGROUND: Several checkpoint pathways employ Wee1-mediated inhibitory tyrosine phosphorylation of cyclin-dependent kinases (CDKs) to restrain cell-cycle progression. Whereas in vertebrates this strategy can delay both DNA replication and mitosis, in yeast cells only mitosis is delayed. This is particularly surprising because yeasts, unlike vertebrates, employ a single family of cyclins (B-type) and the same CDK to promote both S phase and mitosis. The G2-specific arrest could be explained in two fundamentally different ways: tyrosine phosphorylation of cyclin/CDK complexes could leave sufficient residual activity to promote S phase, or S phase-promoting cyclin/CDK complexes could somehow be protected from checkpoint-induced tyrosine phosphorylation. RESULTS: We demonstrate that in Saccharomyces cerevisiae several cyclin/CDK complexes are protected from inhibitory tyrosine phosphorylation, allowing Clb5,6p to promote DNA replication and Clb3,4p to promote spindle assembly, even under checkpoint-inducing conditions that block nuclear division. In vivo, S phase-promoting Clb5p/Cdc28p complexes were phosphorylated more slowly and dephosphorylated more effectively than were mitosis-promoting Clb2p/Cdc28p complexes. Moreover, we show that the CDK inhibitor (CKI) Sic1p protects bound Clb5p/Cdc28p complexes from tyrosine phosphorylation, allowing the accumulation of unphosphorylated complexes that are unleashed when Sic1p is degraded to promote S phase. The vertebrate CKI p27(Kip1) similarly protects Cyclin A/Cdk2 complexes from Wee1, suggesting that the antagonism between CKIs and Wee1 is evolutionarily conserved. CONCLUSIONS: In yeast cells, the combination of CKI binding and preferential phosphorylation/dephosphorylation of different B cyclin/CDK complexes renders S phase progression immune from checkpoints acting via CDK tyrosine phosphorylation.